Direct-acting antiviral treatment against hepatitis C virus infection in HIV-Infected patients – "En route for eradication"?. Issue 3 (September 2017) - ,; Cotte, L.; Chidiac, C.; Ferry, T.; Ader, F.; Biron, F.; Boibieux, A.; Miailhes, P.; Perpoint, T.; Schlienger, I.; Lippmann, J.; Braun, E.; et al.
Summary: Objectives: Direct-Acting Antivirals (DAAs) opened a new era in HCV treatment. We report the impact of HCV treatment in French HIV-HCV coinfected patients. Methods: All HIV-HCV patients from the Dat'AIDS cohort followed between 2012 and 2015 were included. HCV status was defined yearly as naive, spontaneous cure, sustained virological response (SVR12), failure or reinfection. Results: Among 32, 945 HIV-infected patients, 15.2% were positive for anti-HCV antibodies. From 2012 to 2015, HCV incidence rate increased from 0.35%PY to 0.69%PY in MSM, while median incidence was 0.08%PY in other patients. Median reinfection rate was 2.56%PY in MSM and 0.22%PY in other patients. HCV treatment initiation rate rose from 8.2% in 2012 to 29.6% (48.0% in pre-treated patients vs 22.6% in naïve patients). SVR12 rate increased from 68.7% to 95.2%. By the end of 2015, 62.7% of the patients were cured either spontaneously or following SVR. Conclusions: HCV treatment dramatically increased in HIV-HCV patients in France from 2012 to 2015 resulting in HCV cure in nearly two-thirds of the patients in this cohort. Combined with a declining HCV prevalence, the prevalence of active HCV infection among HIV patients will drastically decrease in the forthcoming years. Highlights: The Dat'AIDS cohort covers about 25% of HIV-infected patients in France. DAA are highly effective in a real world cohort of HIV-HCV coinfected patients. In 2015, HCV treatment initiation rate was 29% in HIV-HCV patients in France. By the end of 2015, 63% of patients were cured either spontaneously or following SVR.